Clinical evaluation of the essential oil of "Satureja Hortensis" for the treatment of denture stomatitis - Ali Mohammad Sabzghabaee; Naeimehsadat Davoodi; Behnaz Ebadian; Abolfazl Aslani; Alireza Ghannadi (Wolters Kluwer Medknow Publications, 2012)
Background: The prevalence of denture stomatitis has been shown to vary from 15 to 65% in complete denture wearers. Satureja hortensis L. has been considered to have antinociceptive, anti-inflammatory, antifungal and antimicrobial activities in vitro and exhibits strong inhibitory effect on the growth of periodontal bacteria. The aim of this study was to evaluate the efficacy of a 1% gel formulation of S. hortensis essential oil for the treatment of denture stomatitis. Materials and Methods: A randomized, controlled clinical trial study was conducted on 80 patients (mean age 62.91±7.34) in two parallel groups treated either with S. hortensis essential oil 1% gel or placebo applied two times daily for two weeks. Denture stomatitis was diagnosed by clinical examination and paraclinical confirmation with sampling the palatal mucosa for Candida albicans. Data were analyzed using Chi-squared or Student's t tests. Results: The erythematous lesions of palatal area were significantly reduced (P<0.0001) in the treatment group who applied 1% topical gel of S. hortensis essential oil and Candida colonies count were reduced significantly (P=0.001). Conclusion: Topical application of the essential oil of S. hortensis could be considered as an effective agent for the treatment of denture stomatitis.